Product quality optimization in an integrated biorefinery: Conversion of pistachio nutshell biomass to biofuels and activated biochars via pyrolysis. (1st November 2016) - Işıtan, Seçil; Ceylan, Selim; Topcu, Yıldıray; Hintz, Chloe; Tefft, Juliann; Chellappa, Thiago; Guo, Jicheng; Goldfarb, Jillian L.
Graphical abstract: Highlights: Pyrolysis temperature key variable in manipulating biofuel quality. Pyrolysis temperature does not impact activated biochar surface area. Activation temperature key variable to optimize surface area of pistachio biochar. Statistical model accurately predicts surface area of biochar, especially above 600 m 2 /g. Abstract: An economically viable transition to a renewable, sustainable energy future hinges on the ability to simultaneously produce multiple high value products from biomass precursors. Though there is considerable literature on the thermochemical conversion of biomass to biofuels and biochars, there are few holistic examinations that seek to understand trade-offs between biofuel quality and the associated pyrolysis conditions on activated carbons made from the resulting biochars. Using an Ordinary Least Squares regression analysis, this study probes the impact of pyrolysis and activation temperature on surface areas and pore volumes for 28 carbon dioxide-activated carbons. Activation temperature has the largest single impact of any other variable; increasing the temperature from 800 to 900 °C leads to an increase in surface area of more than 300 m 2 /g. Contrary to some prior results, pyrolysis temperature has minimal effect on the resulting surface area and pore volume, suggesting that optimizing the temperature at which biofuels are extracted will have little impact on carbon dioxide-activated carbons. Increasing pyrolysis temperature increases methane formation but decreases gaseous hydrocarbons. Bio-oil obtained at lower pyrolysis temperatures shows fewer oxygenated compounds, indicating a greater stability, but higher pyrolysis temperatures maximize production of key biorefinery intermediaries such as furans. By analyzing data in such a holistic manner, it may be possible to optimize the production of biofuels and activated carbons from biomass by minimizing the amount of raw materials and energy necessary to maximize fuel quality, surface areas and pore volumes, thereby increasing the economic incentives for thermochemical conversion of biomass.